Systemic Liquidity Shocks and Banking Sector Liquidity Characteristics on the Eve of Liquidity Coverage Ratio Application - The Case of the Czech Republic - Karel Brůna; Naďa Blahová (Journal of Central Banking Theory and Practice, 2016)
The paper contains an analysis of the economic and regulatory concept of bank liquidity in the context of systemic liquidity shock. A formal model analysis shows that the application of liquidity coverage ratio (LCR) based on Basel III will lead to a significant adaptation of banks liquidity management. LCR causes a change in banks liquidity allocation and funding to be less effective and more costly and restrictive for providing credits comparing with economic determinants. It is demonstrated that the application of LCR underestimates actual liquidity position of a bank and leads to allocation ineffectiveness. The empirical part contains simulation of impacts of systemic liquidity shock on the banking sectors ability to withstand the unfavourable credit shock while solvency is maintained. The results confirm the robustness of the Czech banking system ensuing from the systemic surplus of liquidity, high volume of bank capital and its high profitability. The estimations of the VAR model show that the relations between liquidity characteristics of banks, sources of aggregate liquidity shock, interbank market illiquidity and the credit facilities of the Czech National Bank are relatively weak, supporting the conclusion that the banks face liquidity shocks of non-persistent character.
Keywords: G28; G21; G32; 330; LCR; Basel III; liquidity management